2014
DOI: 10.2527/jas.2013-7252
|View full text |Cite
|
Sign up to set email alerts
|

The duration of time that beef cattle are fed a high-grain diet affects feed sorting behavior both before and after acute ruminal acidosis1,2

Abstract: The objective of this study was to determine how duration of time that cattle are fed a high-grain diet affects feed sorting, both before and after an episode of acute ruminal acidosis. Sixteen Angus heifers (261 ± 6.1 kg; BW ± SEM) were assigned to 1 of 4 blocks and fed a backgrounding (BG) diet (60% forage, DM basis). Within block, heifers were randomly assigned to 1 of 2 treatments differing in days fed a high-grain (HG; 9% forage, DM basis, fed ad libitum) diet before a ruminal acidosis challenge: 34 d for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…In our study, the short latency heifers showed to approach the gate could, in part, be explained by consuming the high-energy, low-roughage diet for 30 d before data collection. Indeed, more experience (34 vs. 8 d) with this type of diet results in greater sorting for longer, fibrous particles [ 7 ]. These responses perhaps reflect a more persistent change in internal state [ 29 ], and future work could examine whether the latency to obtain forage depends on the amount of experience with a high-energy, low-roughage diet, as well as how this relates to patterns of rumen pH within and across days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the short latency heifers showed to approach the gate could, in part, be explained by consuming the high-energy, low-roughage diet for 30 d before data collection. Indeed, more experience (34 vs. 8 d) with this type of diet results in greater sorting for longer, fibrous particles [ 7 ]. These responses perhaps reflect a more persistent change in internal state [ 29 ], and future work could examine whether the latency to obtain forage depends on the amount of experience with a high-energy, low-roughage diet, as well as how this relates to patterns of rumen pH within and across days.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers previously found that heifers with more experience (34 vs. 8 d) with a high-concentrate, low-roughage diet show greater sorting for longer feed particles [ 7 ]. Therefore, to minimize possible changes in feeding behavior during data collection, heifers were fed their assigned treatment diet for at least 30 d beforehand while group-housed at the UC Davis feedlot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, further studies are needed to describe the importance of expressing selective intake of diet components by sitatunga. It has been shown that ruminants try to overcome the negative consequences of a sudden drop in rumen pH by selective consumption of structured components and increased saliva production shortly after an episode of rumen acidosis (Schwaiger et al, 2013;DeVries et al, 2014), which may also indicate a higher probability of rumen acidosis when pelleted feed was used in the basal diet. On the one hand, faster eating rate of pelleted diet may increase the probability of rumen acidosis, but on the other, depending on feed processing prior to pelleting and feed composition, pelleted feed may decrease the ruminal OM digestibility, due to faster rumen escape (Górka et al, 2015), and in consequence decreases short-chain fatty acids production in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…When experiencing an acute bout of ruminal acidosis, cows have been shown to sort in favor of the physically effective portion of the diet to alleviate the symptoms of low rumen pH, likely as a result of postingestive feedback (DeVries et al, 2008). Beef cattle have similarly been shown to sort in favor of the longest dietary particles when induced with an acute bout of ruminal acidosis (DeVries et al, 2014a), with those animals experiencing the greatest degree of acidosis demonstrating the greatest selection for long, fibrous particles (DeVries et al, 2014b). To further support the theory that dairy cows alter their preferences when experiencing SARA, Maulfair et al (2013) found that dairy cows experiencing an acidosis challenge selected in favor of a diet that was more physically effective and had lower starch fermentability.…”
Section: Itemmentioning
confidence: 99%